THE IMPACT OF GENERIC COMPETITIVE STRATEGIES ON ORGANIZATIONAL PERFORMANCE. THE EVIDENCE FROM ALBANIAN CONTEXT - Pulaj (Brakaj), Enida; Kume, Vasilika; Cipi, Amali (European Scientific Journal, ESJ, 2015)
One of the main questions that guide researches in management field is why some companies are different and obtain good performance compare to other companies. Nowadays, there has been a growing intensity of competition in all areas of business and this has resulted in greater attention to analyse competitive behaviour under different competitive strategies application and environmental dynamics and complexity. The purpose of this paper is to examine the relationship between competitive strategies and organizational performance. Testing the applicability of Porter`s generic strategies in construction firms we can explain the differences in the performance and comprehend how generic strategies can give them a performance advantage over the rivals. Simple random sampling technique was used to select a sample of 110 companies. The data was be collected using questionnaires and analyzed using ANOVA statistical model. This paper reports findings on the relationship between the Porter`s generic strategies (cost leadership, differentiation) and firm performances. The study found significant positive effects of cost leadership, differentiation and focus strategies on performance. The results of this study would assist the managers to design better competitive strategies they have to compete. According the purpose of this study there are following the qualitative and quantitative methods.